Cyclists or avatars: is virtual cycling filling a short-term void during COVID-19 lockdown? - Rojas-Valverde, D.; Córdoba-Blanco, J. M.; González-Salazar, L. (Managing Sport and Leisure, 2021)
Indoor cycling has been a trend during the COVID-19 pandemic due to the lockdowns and social distancing measures imposed by most countries. Virtual cycling (eCycling) has grown exponentially, and its popularity among amateur and professional cyclists is shown by the fact that they regularly participate in virtual competitions in which people from all over the world interact via streaming. Although eCycling is derived from a traditional sport and adapted to a virtual platform, its future success once real competitions are reinstated has been seriously questioned. This virtual cycling modality has been openly criticized for the potential differences when competing and that it does not represent the true essence of cycling. These questions and the lack of clear guidelines for its competition suggest that eCycling has to go a long way before being considered a sport. This manuscript aims to present some challenges and opportunities regarding how virtual racing could be sustainable over time once the COVID-19 lockdown is over and demonstrate that eCycling was not just filling a short-term void left by real cycling during this pandemic.